The real impact of telaprevir dosage on the antiviral and side effects of telaprevir, pegylated interferon and ribavirin therapy for chronic hepatitis C patients with HCV genotype 1. Issue 3 (31st July 2014) - Oze, T.; Hiramatsu, N.; Yakushijin, T.; Yamada, R.; Harada, N.; Morishita, N.; Oshita, M.; Mita, E.; Ito, T.; Inui, Y.; Inada, M.; Tamura, S.; et al.
Summary Triple therapy with telaprevir, pegylated interferon and ribavirin has been reported to improve antiviral efficacy but have potentially severe adverse effects in patients with chronic hepatitis C. To avoid the severe effects of telaprevir, lowering the dose has been suggested. However, impact of dosage changes on antiviral and adverse effects remains unclear. One hundred and sixty‐six Japanese patients with HCV genotype 1 were treated with triple therapy. The drug exposure of each medication was calculated by averaging the dose actually taken. The overall SVR rate was 82%. The telaprevir discontinuation rate was 26%. The factors associated with discontinuation were an older age (≥65 y.o.) and a higher average dose during treatment. The telaprevir discontinuation rates were 42%, 25% and 14% in patients at ≥35, 25–35 and <25 mg/kg/day of telaprevir and 58% in older patients at ≥35 mg/kg/day of TVR. The factors associated with SVR were treatment‐naïve, relapse to previous treatment, higher average telaprevir dose during treatment and completion of treatment. The SVR rate was higher, at 91%, in patients at 25–35 mg/kg/day of telaprevir than the 71% and 78% observed in those at <25 and ≥35 mg/kg/day of drug. In Japanese patients, a mean telaprevir dose of 25–35 mg/kg/day during treatment can augment its efficacy in triple therapy for patients with HCV genotype 1.